Lipid–oligonucleotide conjugates for bioapplications. Issue 12 (9th July 2020) - Li, Xiaowei; Feng, Kejun; Li, Long; Yang, Lu; Pan, Xiaoshu; Yazd, Hoda Safari; Cui, Cheng; Li, Juan; Moroz, Leonid; Sun, Yujia; Wang, Bang; Li, Xiang; et al.
Abstract: Lipid–oligonucleotide conjugates (LONs) are powerful molecular-engineering materials for various applications ranging from biosensors to biomedicine. Their unique amphiphilic structures enable the self-assembly and the conveyance of information with high fidelity. In particular, LONs present remarkable potential in measuring cellular mechanical forces and monitoring cell behaviors. LONs are also essential sensing tools for intracellular imaging and have been employed in developing cell-surface-anchored DNA nanostructures for biomimetic-engineering studies. When incorporating therapeutic oligonucleotides or small-molecule drugs, LONs hold promise for targeted therapy. Moreover, LONs mediate the controllable assembly and fusion of vesicles based on DNA-strand displacements, contributing to nanoreactor construction and macromolecule delivery. In this review, we will summarize the general synthesis strategies of LONs, provide some characterization analysis and emphasize recent advances in bioanalytical and biomedical applications. We will also consider the relevant challenges and suggest future directions for building better functional LONs in nanotechnology and materials-science applications.